Per Jacobsson Lecture : The Federal Reserve and the Global Economy. (per Jacobson lecture, 2015)
As the Federal Reserve's statutory objectives are defined as specific goals for the U.S. economy-to pursue maximum sustainable employment and price stability-and its policy decisions are targeted to achieve these dual objectives, there might seem to be little need for its policymakers to pay attention to developments outside the United States. But such an inference would be incorrect: the state of the U.S. economy is significantly affected by the state of the world economy, and of course, actions taken by the Federal Reserve influence economic conditions abroad, which in turn spill back on the evolution of the U.S. economy and therefore must be taken into account in the Federal Reserve's monetary policy choices. This Per Jacobsson Lecture first reviews the effect of the Federal Reserve's monetary policies on the rest of the global economy, particularly emerging market economies. It then addresses prospective outcomes and possible risks associated with the normalization of the Federal Reserve's policies. Finally, it discusses the Federal Reserve's responsibilities in the world economy.